Inuit man performing with Drum Dancers - Jim Mys
Caption on verso reads: member of Eskimo [Inuit] Drum Dancers - Native Peoples. Photo property of Mariposa Folk Festival. Please credit Jim Mys." Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada